2010
DOI: 10.1002/ajmg.c.30284
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral features in young adults with FG syndrome (Opitz–Kaveggia syndrome)

Abstract: Opitz and Kaveggia [1974] reported on a family of 5 affected males with distinctive facial appearance, mental retardation, macrocephaly, imperforate anus and hypotonia. Risheg et al. [2007] identified an identical mutation (p.R961W) in MED12 in 6 families with Opitz-Kaveggia syndrome, including a surviving affected man from the original family reported in 1974. The previously described behavior phenotype of hyperactivity, affability, and excessive talkativeness is very frequent in young boys with FG syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…There is a consistent behavior phenotype in males with FG syndrome and this syndrome should be considered in males who present with developmental delay and a behavioral phenotype of hyperactivity, affability, and excessive talkativeness along with the distinctive clinical features of FG syndrome [Graham et al, 1999; Risheg et al, 2007; Clark et al, 2009; Graham et al, 2010]. Males with the recurrent R961W mutation in MED12 have strengths in socialization and daily living skills, despite their communicative deficits [Graham et al, 2008], and their strengths in socialization skills may mask their communicative deficits.…”
Section: Opitz-kaveggia (Fg) Syndromementioning
confidence: 99%
“…There is a consistent behavior phenotype in males with FG syndrome and this syndrome should be considered in males who present with developmental delay and a behavioral phenotype of hyperactivity, affability, and excessive talkativeness along with the distinctive clinical features of FG syndrome [Graham et al, 1999; Risheg et al, 2007; Clark et al, 2009; Graham et al, 2010]. Males with the recurrent R961W mutation in MED12 have strengths in socialization and daily living skills, despite their communicative deficits [Graham et al, 2008], and their strengths in socialization skills may mask their communicative deficits.…”
Section: Opitz-kaveggia (Fg) Syndromementioning
confidence: 99%
“…Germline mutations of MED12 gene have been reported in the Opitz–Kaveggia and Lujan–Fryns syndromes, which are characterized by congenital anomalies and intellectual disability (Taatjes 2010). Evidence has showed that MED12 performs both general and gene-specific roles to regulate gene expression (Graham et al 2010; Taatjes 2010). Nevertheless, the explanation for the high occurrence of MED12 gene mutations and the functional roles of these mutations in the tumorigenesis of uterine fibroids remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Risheg found that there are frequent mutations in the twenty-fi rst exon of MED12 of FG syndrome patients, which results in C2881T and R961W mutations in the protein. Thereafter, the relationship between FG syndrome and mutations in MED12 was confi rmed by several other groups (Opitz and Kaveggia, 1974;Risheg et al, 2007;Graham et al, 2008;Graham et al, 2010). In addition, Rump P and colleagues found that three cousins suffering from FG syndrome all bear a mutation (G958E) in MED12, suggesting that the G958E mutation may also cause FG syndrome (Rump et al, 2011).…”
Section: Med12 Mutation and The X-linked Mental Retardationmentioning
confidence: 92%